2008
DOI: 10.1091/mbc.e08-02-0227
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin–Proteasome-dependent Degradation of a Mitofusin, a Critical Regulator of Mitochondrial Fusion

Abstract: The mitochondrion is a dynamic membranous network whose morphology is conditioned by the equilibrium between ongoing fusion and fission of mitochondrial membranes. In the budding yeast, Saccharomyces cerevisiae, the transmembrane GTPase Fzo1p controls fusion of mitochondrial outer membranes. Deletion or overexpression of Fzo1p have both been shown to alter the mitochondrial fusion process indicating that maintenance of steady-state levels of Fzo1p are required for efficient mitochondrial fusion. Cellular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
169
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(185 citation statements)
references
References 42 publications
11
169
2
1
Order By: Relevance
“…An F-box was identified at the N terminus of the MUS-10 protein (Figure 5), suggesting that it belongs to the F-box protein family whose members are normally components of SCF E3 ubiquitin ligase complexes that direct proteins to the 26S proteasome, ultimately leading to their degradation. These findings are concurrent with the hypothesis that SCF complexes can regulate mitochondrial function (Cohen et al 2008;Deng et al 2008). A YccV-like domain, which has been shown to bind hemimethylated DNA (D'Alencon et al 2003), was also observed in MUS-10, suggesting that it may be capable of interacting with DNA ( Figure 5).…”
Section: Resultssupporting
confidence: 77%
“…An F-box was identified at the N terminus of the MUS-10 protein (Figure 5), suggesting that it belongs to the F-box protein family whose members are normally components of SCF E3 ubiquitin ligase complexes that direct proteins to the 26S proteasome, ultimately leading to their degradation. These findings are concurrent with the hypothesis that SCF complexes can regulate mitochondrial function (Cohen et al 2008;Deng et al 2008). A YccV-like domain, which has been shown to bind hemimethylated DNA (D'Alencon et al 2003), was also observed in MUS-10, suggesting that it may be capable of interacting with DNA ( Figure 5).…”
Section: Resultssupporting
confidence: 77%
“…Similar OMM rupture has been observed in apoptotic cells (49 -51), but we detected neither activation of caspase-3 nor nuclear fragmentation in these cells (data not shown). The involvement of the ubiquitin-proteasome system including other E3 ligases in OMM protein degradation and quality control has been reported (52)(53)(54)(55)(56)(57). Parkin may also have a role in quality control of mitochondria through turnover of OMM proteins under pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…DRP1 semble être le substrat d'autres ubiquitine ligases et ses propriétés (activité, recrutement, stabilité) sont également modifiées par phosphorylation et SUMOylation [23]. Chez la levure, les niveaux de Fzo1 sont contrôlés par un processus de dégradation indépendant ou dépendant du protéasome [24,25]. Chez les mammifères, MFN2 est phosphorylée par la protéine kinase A (PKA), interagit avec une ubiquitine ligase (MITOL/ MARCH5) et son niveau est augmenté par des inhibiteurs du protéasome [10].…”
Section: Régulation De La Fusion/fission Des Mitochondriesunclassified